DIDACTIC POTENTIAL OF HUMANITIES IN DEVELOPING TRANSFORMATIVE COMPETENCIES AMONG COMPUTER ENGINEERING AND INFORMATION TECHNOLOGY UNDERGRADUATES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In the recent decades harnessing the advanced information technologies and their tremendous potential to improve the quality of life for people all over the world is becoming an urgent need than a luxury. Knowing full well that as an innovative student-centred learning paradigm Education 4.0 creates favourable prerequisites for developing valuable professional skills, abilities and knowledge among Computer Engineering and Information Technology undergraduates, the researchers assumed that it also might be effective in preparing them for challenges of the contemporary world through developing their transformative competencies while studying the humanities. The paper aims to reveal the didactic potential of humanities for developing Computer Engineering and Information Technology undergraduates’ transformative competencies. The researchers carried out an exploratory study in five Ukrainian universities using an online survey conceived and developed by a team of researchers. A total of 275 respondents selected by means of a purposeful sampling method took part in the survey. The study found that humanities (1) are more likely to apply various learning activities which can be done both individually and in groups than technical disciplines and (2) have much broader potential for developing all key constructs of transformative competencies among Computer Engineering and Information Technology undergraduates than technical disciplines. The results enabled the researchers to formulate recommendations for university teachers of humanities on how to develop transformative competences among Computer Engineering and Information Technology undergraduates. The combination of challenge-based learning (CBL) and activity-based learning (ABL) is being considered as a major methodological approach of Education 4.0 for developing transformative competences among Computer Engineering and Information Technology undergraduates. Scientific novelty of research consists in revealing and describing the didactic potential of humanities for developing Computer Engineering and Information Technology undergraduates’ transformative competencies.